2017
DOI: 10.5902/2179460x21938
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus Thuringiensis Var. Israelensis Como Alternativa Para O Controle Populacional De Aedes Aegypti (Linnaeus, 1762) (Diptera: Culicidae)

Abstract: Dengue, chikungunya and zika are among the major problems to public health problem in the world. In the absence of vaccine, the only known alternative to prevention is to control the mosquito. Among the methods of control, using biological strains of Bacillus thuringiensis israelensis (Bti) has stood out for its efficiency and security in the application. This study aimed to evaluate the efficiency of Bti to control the population of the Aedes aegypti mosquito in junkyards  and recycling centers of Chapecó, Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A study in Brazil using Bti in containers in recycling and junkyard showed an 89.6% reduction in larvae. 27…”
Section: Discussionmentioning
confidence: 99%
“…A study in Brazil using Bti in containers in recycling and junkyard showed an 89.6% reduction in larvae. 27…”
Section: Discussionmentioning
confidence: 99%
“…Bt is a Gram-positive bacterium known for its toxicity and specificity towards insect hosts due to its ability to produce and release crystal proteins (Cry and Cyt) during the sporulation stage [3]. Bacillus thuringiensis serovar israelensis (Bti) is one of the subspecies' most effective larvicides for mosquito control, being recommended by the World Health Organization (WHO) [4,5]. Bti produces Cry and Cyt crystals (Cry4Aa, Cry4Ba, Cry10Aa, Cry11Aa, Cyt1Aa, and Cyt2Ba) that exhibit toxicity against mosquito species from the genus Aedes, Anopheles, and Culex, and for the black fly (Simuliidae) [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Description based on Blastx from NCBI 4. The number of peptide sequences that are unique to the protein 5. The percentage of the protein sequence covered by identified peptides 6.…”
mentioning
confidence: 99%
“…Significant reduction was observed in the number of breeding sites of A. aegypti in places treated with Bti compared with those that were not (checks) because these had five times more breeding sites than did treated ones. In general, numbers of mosquito eggs and larvae were 89% less with the applied product (Lutinski et al 2017).…”
Section: Introductionmentioning
confidence: 99%